Review: Theological reflections on "Gangnam Style": A racial, sexual, and cultural critique, by Grace Ji-Sun Kim and Joseph Cheah - TSE, Justin Kh (Institutional Knowledge at Singapore Management University, 2017)
When I started reading Joseph Cheah and Grace Ji-Sun Kim’s Theological Reflections on “Gangnam Style,” I expected a close reading of the viral pop song from Korean artist Psy [Park Jae-sang] called “Gangnam Style.” However, perhaps the title is a little misleading; most of the book is neither “theological,” nor a series of “reflections,” nor even about Psy or “Gangnam Style.” It is about Asian and Asian American theology.